Effect of Gambogic Acid–Loaded Porous-Lipid/PLGA Microbubbles in Combination With Ultrasound-Triggered Microbubble Destruction on Human Glioma - Wang, Feng; Dong, Lei; Wei, Xixi; Wang, Yongling; Chang, Liansheng; Wu, Hongwei; Liu, Shuyuan; Chang, Yuqiao; Yin, Yaling; Luo, Xiaoqiu; Jia, Xiaojian; Yan, Fei; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Gambogic acid (GA) is a highly effective antitumor agent, and it is used for the treatment of a wide range of cancers. It is challenging to deliver drugs to the central nervous system (CNS) due to the inability of GA to cross the blood-brain barrier (BBB). Studies have shown that ultrasound-targeted microbubble destruction (UTMD) can be used for transient and reversible BBB disruption, significantly facilitating intracerebral drug delivery. We first prepared GA-loaded porous-lipid microbubbles (GA/PLGA MBs), and an in vitro BBB model was established. The cell viability was detected by cck-8 reagent and flow cytometry. The results indicate that U251 human glioma cells were killed by focused ultrasound (FUS) combined with GA/PLGA. FUS combined with GA/PLGA microbubbles was capable of locally and transiently enhancing the permeability of BBB under certain conditions. This conformational change allows the release of GA to extracellular space. This study provides novel targets for the treatment of glioma.